Telomere elongation upon transfer to callus culture reflects the reprogramming of telomere stability control in Arabidopsis - Sováková, Pavla Polanská; Magdolenová, Alžbeta; Konečná, Klára; Rájecká, Veronika; Fajkus, Jiří; Fojtová, Miloslava (Plant molecular biology, 2018)
Standard pathways involved in the regulation of telomere stability do not contribute to gradual telomere elongation observed in the course of A. thaliana calli propagation. Genetic and epigenetic changes accompanying the culturing of plant cells have frequently been reported. Here we aimed to characterize the telomere homeostasis during long term callus propagation. While in Arabidopsis thaliana calli gradual telomere elongation was observed, telomeres were stable in Nicotiana tabacum and N. sylvestris cultures. Telomere elongation during callus propagation is thus not a general feature of plant cells. The long telomere phenotype in Arabidopsis calli was correlated neither with changes in telomerase activity nor with activation of alternative mechanisms of telomere elongation. The dynamics of telomere length changes was maintained in mutant calli with loss of function of important epigenetic modifiers but compromised in the presence of epigenetically active drug zebularine. To examine whether the cell culture-induced disruption of telomere homeostasis is associated with the modulated structure of chromosome ends, epigenetic properties of telomere chromatin were analysed. Albeit distinct changes in epigenetic modifications of telomere histones were observed, these were broadly stochastic. Our results show that contrary to animal cells, the structure and function of plant telomeres is not determined significantly by the epigenetic character of telomere chromatin. Set of differentially transcribed genes was identified in calli, but considering the known telomere- or telomerase-related functions of respective proteins, none of these changes per se was apparently related to the elongated telomere phenotype. Based on our data, we propose that the disruption in telomere homeostasis in Arabidopsis calli arises from the interplay of multiple factors, as a part of reprogramming of plant cells to long-term culture conditions.
Keywords: proteiny huseníčku; histony; Cytidine; RNA, Messenger; druhová specificita; Genes, Plant; Regeneration; mutace; telomerasa; Arabidopsis thaliana; Arabidopsis; Chromosome stability; epigeneze genetická; Tissue Culture Techniques; Arabidopsis Proteins; Epigenetics; techniky tkáňových kultur; Species Specificity; regenerace; Telomere Homeostasis; chromatin; cytidin; Chromatin; Nicotiana; Telomerase; Regenerated plants; telomery; Ecotype; Histones; homeostáza telomer; Mutation; rostlinné geny; ekotyp; messenger RNA; tabák; Callus; Telomere; Epigenesis, Genetic